2003
DOI: 10.1248/cpb.51.888
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Highly Practical Oxidation of Primary Alcohols to Acids Mediated by 2,2,6,6-Tetramethyl-1-piperidinyloxy (TEMPO)

Abstract: Conversion of alcohols to the corresponding acids is an important transformation in organic and pharmaceutical synthesis and a number of methods have been developed to date. These include the classical and most well known methods using chromium(VI) oxides, represented by Jones reagent, 1,2) Collins reagent, 3,4) and pyridinium chlorochromate (PCC). 5,6) Although these methods are commonly applied on a laboratory scale, and are efficient enough to give materials in gram quantities, the highly toxic chromium sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Nitroxide/hypochlorite-and chlorite-mediated oxidations have been carried out in two steps, albeit in the same reaction vessel. 187 The primary alcohol is oxidized to the aldehyde with sodium hypochlorite and TEMPO. Then, sodium chlorite is added to the reaction mixture to complete the oxidation.…”
mentioning
confidence: 99%
“…Nitroxide/hypochlorite-and chlorite-mediated oxidations have been carried out in two steps, albeit in the same reaction vessel. 187 The primary alcohol is oxidized to the aldehyde with sodium hypochlorite and TEMPO. Then, sodium chlorite is added to the reaction mixture to complete the oxidation.…”
mentioning
confidence: 99%
“…It is found that a slightly lower pH, of 4-6, enhances the reactivity of the latter step. 79 For further examples of tandem reactions, see Section 12.10.…”
Section: Oxidations Leading To Linear Carboxylic Acidsmentioning
confidence: 99%
“…The transformation of aldehydes to carboxylic acids is an important reaction in organic synthesis. The commonly used oxidants for this transformation are NaClO 2 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], K 2 Cr 2 O 7 [ 8 , 9 ], pyridinium chlorochromate [ 10 ], quinolinium dichromate [ 11 , 12 , 13 ], KMnO 4 [ 14 , 15 , 16 ], H 2 O 2 [ 17 , 18 ] and so on. Organic solvents such as CH 3 CN, CH 2 Cl 2 , cyclohexane, formic acid and benzene are usually needed.…”
Section: Introductionmentioning
confidence: 99%